1973
DOI: 10.1115/1.3450087
|View full text |Cite
|
Sign up to set email alerts
|

Velocity, Temperature, and Turbulence Measurements in Air for Pipe Flow With Combined Free and Forced Convection

Abstract: Experimental results are presented for velocity and temperature profiles and for the turbulence quantities vz′ t′ and vzt, for up-flow of air in a vertical pipe with constant heat flux at Reynolds numbers of 5000 to 14,000. The measurements show that, with increasing heat flux, superimposed free convection effects cause marked distortion of the flow structure at low Reynolds numbers, with the velocity maximum moving from the tube center to a position near the wall. The axial turbulence intensity, vz′, is depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 0 publications
7
41
0
Order By: Relevance
“…In their DNS work, You et al [18] explained that while their results did not agree well with experimental data obtained by imposing the total pressure drop (e.g., Parlatan et al [27]), they observed closer agreement with those obtained by measurement of velocity gradient instead (e.g., Carr et al [26]). In addition, discrepancies are likely to arise from different methods of measuring c f .…”
Section: Results Of Local Nusselt Number and Friction Coefficientsupporting
confidence: 56%
See 2 more Smart Citations
“…In their DNS work, You et al [18] explained that while their results did not agree well with experimental data obtained by imposing the total pressure drop (e.g., Parlatan et al [27]), they observed closer agreement with those obtained by measurement of velocity gradient instead (e.g., Carr et al [26]). In addition, discrepancies are likely to arise from different methods of measuring c f .…”
Section: Results Of Local Nusselt Number and Friction Coefficientsupporting
confidence: 56%
“…In the case of the LS model this is, at least in part, related to its underprediction of c f0 by about 8% (Table 5). In turn, this results in an earlier onset of friction coefficient enhancement compared with the experimental results of Carr et al [26] and DNS data. In comparison with the LS model, the results of the Suga model indicate a steeper enhancement gradient.…”
Section: Results Of Forced Convectionsupporting
confidence: 43%
See 1 more Smart Citation
“…Four simulations are reported by You et al and these are detailed in Table 7 Also represented in Fig. 4 are the data of Steiner [1971], Carr et al [1973] and Parlatan et al [1996]. While these data were obtained for values of Re, Pr, and Gr different from those of You et al, all are cast in terms of Bo.…”
Section: 12) Mixed Convectionmentioning
confidence: 99%
“…Experimental studies of ascending mixed convection air flows include the works of Steiner [1971], Carr et al [1973], Polyakov and Shindin [1988], Vilemas et al [1992] and Shehata and McEligot [1998]. Results for water flows are reported by Parlatan et al [1996].…”
Section: 2) Review Of Previous Workmentioning
confidence: 99%